Cádmio, chumbo, cromo, mercúrio e níquel nos rios do estado de São Paulo e em peixes do Rio Sorocaba (São Paulo, Brasil) - Castro, Neemias de [UNESP] (2002)
To verify the levels of concentration of some heavy metals in fishes from Sorocaba river (São Paulo, Brazil) and evaluate if this contamination offers health risks to the fishermen, 63 samples of fishes collected from four points along the river were studied for cadmium, lead, chromium, nickel and mercury, with emphasis in this last, since it is the most toxic and most probable as a fish contaminant. Analyzing muscle samples by cold vapor atomic absorption spectrometry it was shown that the fishes are not contaminated. None of the five metals studied were present in prohibitive level and the fishes could be judged secure for human consume. It was also analyzed data from four years of cadmium, lead, chromium, nickel and mercury monitoring made by CETESB, from 1997 to 2000, in water from the main rivers of the State of São Paulo. The study pointed out that the majority of the monitored rivers still present contamination by those metals in a level that requires an improvement of the pollution control actions.